Pre‐service teacher perspectives towards pedagogical uses of non‐native and native speech samples. (17th November 2014) - Litzenberg, Jason
Abstract : This article reports on part of a quantitative/ qualitative study investigating the attitudes of pre‐service English language teachers in the United States towards native/non‐native Englishes in interaction. The study is unique to language attitude research in that participants evaluate speech‐in‐action of multiple speakers rather than isolated speech samples. It is therefore relevant to linguistic approaches that emphasize communication, such as English as a Lingua Franca (ELF), which until now has been under‐represented in North American research. Results indicate a willingness among pre‐service teachers to use non‐native Englishes as pedagogical models for certain language skills and course types. Implications for English language teacher training are discussed.